Public expenditure tracking in Africa: Trends and composition - Fan, Shenggen; Omilola, Babatunde; Lambert, Melissa (International Food Policy Research Institute, 2009)
Public spending is one of the most effective instruments in promoting agricultural growth and reducing poverty in developing countries. Thus, monitoring public spending in agriculture is crucial. Agricultural growth also depends upon non-agriculture expenditures such as rural infrastructure, health and education. Since these investments may have differential productivity and poverty reduction effects, it is important to monitor spending in these sectors as well. This paper has two main objectives. The first objective is to define, measure and review the trends of government expenditures and their composition across different world regions over time with a particular focus on Africa. Aid for agriculture is also reviewed as it often accounts for a large share of government spending in agriculture and it reflects donors’ priority in supporting agriculture in Africa. The second objective is to track progress of the commitment made by African governments at the African Union Summit in Maputo, Mozambique in 2003 to increase public spending in agriculture to at least 10 percent of total government budgetary resources.